Social capital : the neglected criterion of women entrepreneurs success - Rajennd Muniady; Abdullah Al Mamun; P. Yukthamarani Permarupan (Penerbit Universiti Malaysia Kelantan, 2018)
Entrepreneurship forms a crucial part of the economic system through out the globe. Moreover, it is the main key to economic growth and human development, for nations aiming and coping with competitiveness and globalisation. In between the fast paced world, more and more women take up responsibility and not-letting go of opportunities to venture the world of entrepreneurs. Despite the challenges of capital, skill and equal opportunity, women entrepreneurs make headlines every now and then. However, the challenges remain real for those who engage in small scale entrepreneurship activities in the form of financial capital, human capital and social capital. This book attempts to bring understanding on the importance of social capital, as it is the most underrated capital among the three capitals above mentioned. The structure and flow of the book is in such a way (step by step, research based structure) to make it clear on how the authors concluded that social capital creates competitive advantage which is an important factor for the success of women entrepreneurs.